A report of 2 cases of Cornelia de Lange syndrome (CdLS) and an analysis of clinical and genetic characteristics in a Chinese CdLS cohort. Issue 2 (24th December 2019) - Li, Shuo; Miao, Hui; Yang, Hongbo; Wang, Linjie; Gong, Fengying; Chen, Shi; Zhu, Huijuan; Pan, Hui
Abstract: Background: Cornelia de Lange syndrome (CdLS) is a rare dominantly inherited developmental disorder with an estimated prevalence of 0.5–10:100, 000 and no racial disparity in prevalence. The aim of this study was to present two unrelated Chinese CdLS individuals with mutations in NIPBL and to perform a comprehensive analysis of a Chinese cohort with CdLS. Subjects and methods: Two unrelated Chinese patients complaining of short stature were referred to the outpatient department of Peking Union Medical College Hospital (PUMCH). Their clinical data at birth and at the most recent assessment were collected. Mutation analysis was carried out by whole exome sequencing. Twenty‐four Chinese cases with CdLS were identified through a systematic review of the literature published between 1987 and 2017. Results: Two patients presented with typical phenotypes, characteristic complications of CdLS and mutations in the NIPBL gene. The average age at diagnosis of the 26 Chinese cases was higher than that of other cohorts. The frequencies of characteristic manifestations of CdLS were similar with those of other populations. Conclusions: By investigating 26 Chinese cases of CdLS, we observed that the clinical data and gene variants in the Chinese cohort of CdLS patients were generally in accordance with those of other populations. Abstract : We found two patients presented with typical phenotypes, characteristic complications of CdLS and mutations in the NIPBL gene. By investigating 26 Chinese cases of CdLS, we observed that the clinical data and gene variants in the Chinese cohort of CdLS patients were generally in accordance with those of other populations. To date, the NIPBL‐LOVD database (Leiden open variation database) describes 266 unique DNA variants, reported in 352 individuals (last accessed July 2017) which include substitutions (65.1%, 229/352), deletions (23.9%, 84/352), duplications (8.8%, 31/352), insertions/deletions (1.4%, 5/352) and insertions (0.9%, 3/352) (Figure 4).